Unregulated hunting and genetic recovery from a severe population decline: the cautionary case of Bulgarian wolves - Moura, Andre E; Tsingarska, Elena; D browski, Michał J; Czarnomska, Sylwia D; Jędrzejewska, Bogumiła; Pilot, Małgorzata (Conservation genetics, 2014)
European wolf (Canis lupus) populations have suffered extensive decline and range contraction due to anthropogenic culling. In Bulgaria, although wolves are still recovering from a severe demographic bottleneck in the 1970s, hunting is allowed with few constraints. A recent increase in hunting pressure has raised concerns regarding long-term viability. We thus carried out a comprehensive conservation genetic analysis using microsatellite and mtDNA markers. Our results showed high heterozygosity levels (0.654, SE 0.031) and weak genetic bottleneck signals, suggesting good recovery since the 1970s decline. However, we found high levels of inbreeding (F IS = 0.113, SE 0.019) and a N ₑ/N ratio lower than expected for an undisturbed wolf population (0.11, 95 % CI 0.08–0.29). We also found evidence for hybridisation and introgression from feral dogs (C. familiaris) in 10 out of 92 wolves (9.8 %). Our results also suggest admixture between wolves and local populations of golden jackals (C. aureus), but less extensive as compared with the admixture with dogs. We detected local population structure that may be explained by fragmentation patterns during the 1970s decline and differences in local ecological characteristics, with more extensive sampling needed to assess further population substructure. We conclude that high levels of inbreeding and hybridisation with other canid species, which likely result from unregulated hunting, may compromise long-term viability of this population despite its current high genetic diversity. The existence of population subdivision warrants an assessment of whether separate management units are needed for different subpopulations. Our study highlights conservation threats for populations with growing numbers but subject to unregulated hunting.